Samochody wycofane z eksploatacji – kluczowe zagadnienia związane z systemem recyklingu - Kubiak, Teresa (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2022)
W artykule przedstawiono problemy związane z samochodami wycofywanymi z eksploatacji, strukturę wiekową parku samochodowego w krajach Unii Europejskiej i w Polsce, oraz prognozy w tym zakresie na kolejne lata. Gwałtowny wzrost liczby samochodów wprowadza konieczność racjonalnej gospodarki odpadami pochodzącymi z ich eksploatacji i złomowania pojazdów. Obecna struktura wiekowa krajowego parku, w której znaczną część stanowią pojazdy stare i wyeksploatowane, przyczynia się do stałego wzrostu łącznej masy odpadów samochodowych.

To achieve the stated goal of the thesis, several research tasks have been planned and completed. Detailed account of this research was introduced in three parts of the thesis. In the first part of the thesis - by way of introduction - the literature discussed is analyzed as well as the presentation of the main problems of the recycling of end-of-life vehicles. This section also introduces the experience of Western European countries in organizing end-of- life vehicle (ELV) recycling systems. The size and aging of the car market in several selected EU countries, including Poland, is presented. A quantitative and qualitative analysis of the recovery of waste and recycled materials has been carried out. In this part of the thesis, the prospects of different recycling methods and specific waste recycling processes, including their environmental and economic aspects, are presented.
Keywords: struktura parku samochodowego; samochód wycofany z eksploatacji (SWE); recykling; stacja demontażu samochodów; wpływ recyklingu SWE na środowisko przyrodnicze; structure of the car park; end-of-life vehicles (ELV); recycling; car dismantling station; impact of ELV recycling on the natural environment